Contribution of Liver and Pancreatic Islet Crosstalk to β-Cell Function/Dysfunction in the Presence of Fatty Liver - López-Bermudo, Lucía; Luque-Sierra, Amparo; Maya-Miles, Douglas; Gallego-Durán, Rocío; Ampuero, Javier; Romero-Gómez, Manuel; Berná, Genoveva; Martín, Franz (Frontiers in Endocrinology, 2022)
Tissue-to-tissue crosstalk regulates organ function, according to growing data. This phenomenon is relevant for pancreatic β-cells and the liver, as both tissues are involved in glucose homeostasis and lipid metabolism. The ability to fine-tune regulation and adaptive responses is enabled through communication between pancreatic β-cells and the liver. However, the crosstalk between both tissues changes when metabolic dysregulation is present. Factors and cargo from extracellular vesicles (EVs) released by liver and pancreatic β-cells that reach the circulation form the words of this interaction. The molecules released by the liver are called hepatokines and are usually secreted in response to the metabolic state. When hepatokines reach the pancreatic islets several mechanisms are initiated for their protection or damage. In the case of the crosstalk between pancreatic β-cells and the liver, only one factor has been found to date. This protein, pancreatic derived factor (PANDER) has been proposed as a novel linker between insulin resistance (IR) and type 2 diabetes mellitus (T2D) and could be considered a biomarker for non-alcoholic fatty liver disease (NAFLD) and T2D. Furthermore, , the cargo released by EVs, mainly miRNAs, plays a significant role in this crosstalk. A better knowledge of the crosstalk between liver and pancreatic β-cells is essential to understand both diseases and it could lead to better prevention and new therapeutic options.